Covalent Organic Frameworks Enabling Site Isolation of Viologen‐Derived Electron‐Transfer Mediators for Stable Photocatalytic Hydrogen Evolution. Issue 17 (11th March 2021) - Mi, Zhen; Zhou, Ting; Weng, Weijun; Unruangsri, Junjuda; Hu, Ke; Yang, Wuli; Wang, Changchun; Zhang, Kai A. I.; Guo, Jia
Abstract: Electron transfer is the rate‐limiting step in photocatalytic water splitting. Viologen and its derivatives are able to act as electron‐transfer mediators (ETMs) to facilitate the rapid electron transfer from photosensitizers to active sites. Nevertheless, the electron‐transfer ability often suffers from the formation of a stable dipole structure through the coupling between cationic‐radical‐containing viologen‐derived ETMs, by which the electron‐transfer process becomes restricted. Herein, cyclic diquats, a kind of viologen‐derived ETM, are integrated into a 2, 2′‐bipyridine‐based covalent organic framework (COF) through a post‐quaternization reaction. The content and distribution of embedded diquat‐ETMs are elaborately controlled, leading to the favorable site‐isolated arrangement. The resulting materials integrate the photosensitizing units and ETMs into one system, exhibiting the enhanced hydrogen evolution rate (34600 μmol h −1 g −1 ) and sustained performances when compared to a single‐module COF and a COF/ETM mixture. The integration strategy applied in a 2D COF platform promotes the consecutive electron transfer in photochemical processes through the multi‐component cooperation. Abstract : Viologen‐derived electron‐transfer mediators (ETMs) are integrated into a 2, 2′‐bipyridine‐containing covalent organic framework (COF) by a controllable post‐synthetic method. The site‐isolated ETM modules cooperate well with photosensitizer modules on the platform of COFs for enhanced electron‐transfer ability, thereby remarkably promoting the photocatalytic H2 evolution performance (34600 μmol h −1 g −1 ) from water splitting.